Magnetic Resonance Imaging-Based Evaluation of Healing Status and Injury Sites of the Acromioclavicular Ligament Complex and Their Association with Reduction Loss after Hook Plate Fixation - Cho, Young Tak; Lee, Sanghyeon; Yang, Ik; Liu, Jiaqi; D’lima, Darryl D.; Kim, Jung Youn (Clinics in orthopedic surgery, 2025)
Background: A limitation of hook plate (HP) fixation for treating acromioclavicular (AC) joint dislocations is reduction loss after plate removal. While the healing of the coracoclavicular (CC) ligament is generally reliable after HP fixation, the healing status of the acromioclavicular ligament complex (ACLC) remains less understood. Our hypothesis was that ACLC healing failure would increase the risk of reduction loss. Methods: Patients who underwent HP fixation within 2 weeks of injury and had preoperative and post-HP removal magnetic resonance imaging (MRI) from May 2018 to May 2023 for acute Rockwood type III or V AC joint dislocations were retrospectively reviewed. Reduction loss was defined as a coracoclavicular distance (CCD) ratio (CCD of the injured side / uninjured side × 100) greater than 150 at final follow-up. Ligament healing was assessed using the Ihara grade, with grades 1 and 2 considered healed. The tear sites of the ACLC were identified with bony attachment and mid-substance site. Results: A total of 33 patients were included. CC ligaments healed in all cases. The mean follow-up period was 11.8 ± 4.1 months. The mean time to HP removal was 3.4 ± 0.8 months postoperatively. ACLC healing was observed in 21 patients, and non-healing in 12 patients. Reduction loss was significantly more frequent in the non-healing group (83.3%, 10 / 12) than in the healing group (23.8%, 5 / 21) (OR, 16.0; 95% CI, 2.59–98.77; p = 0.001). The ACLC healing failure rate was significantly higher in the bony attachment tear group (52.6%, 10 / 19) than in the mid-substance tear group (14.3%, 2 / 14) (OR, 6.67; 95% CI, 1.16–38.94; p = 0.024). Reduction loss was also significantly more frequent in bony attachment tears (63.2%, 12 / 19) than in mid-substance tears (21.4%, 3 / 14) (OR, 6.29; 95% CI, 1.29–30.54; p = 0.017). Conclusions: Reduction loss after HP fixation for treating AC joint dislocations was associated with the healing status and tear sites of the ACLC. Particularly, bony attachment site tears demonstrated lower healing potential and a higher risk of reduction loss, suggesting that additional procedures beyond HP fixation should be considered when such tears are identified preoperatively on MRI. KCI Citation Count: 0